Nyeri Dada pada Pasien Sindrom Koroner Akut (SKA) dengan Terapi Hangat (Thermotherapy): A Literature Review - Harista, Dessy Rindiyanti; Nurseskasatmata, Satria Eureka; Kholis, Anja Hesnia; Hilfida, Nurullia Hanum; Lailiah, Novianti (Universitas Nazhatut Thullab Al- Muafa Sampang, 2025)
Introduction: Chest pain is a common complaint in patients with Acute Coronary Syndrome (ACS). One of the non-pharmacological therapies that can be applied to treat chest pain is thermotherapy or heat therapy. Local thermotherapy can reduce or relieve chest pain by suppressing metabolites as pain mediators. Objective: The purpose of this review is to identify the effect of thermotherapy on chest pain in patients with SCA. Methods: the method used was literature review, using electronic journal databases. Databases used include Pubmed, Science Direct, and Proquest with keywords that match chest pain, ACS, and thermotherapy. Results: The results of the literature search obtained 3 articles from databases and 3 articles from handsearch. All the literature found obtained results that had a significant effect or positive results on reducing the intensity of chest pain in patients with Acute Coronary Syndrome (ACS) with thermotherapy or heat therapy. Conclusion: Thermotherapy or heat therapy can be used as an alternative therapy to reduce chest pain in ACS patients.